Factors affecting UUM students’ green practices - Cha, Rong Lin; Hashim, Rushanim (Universiti Utara Malaysia, 2020)
Environment problem is one of the critical global issues. Most of environmental impacts is brought by human behaviour such as global warming and pollution. These impacts not only bring negative effect to the environment but also to human lives. Therefore, the idea of green practices is becoming increasingly important. Green practices concern to ‘environmental-friendly practices’ with the aim to reduce the environmental impacts. This study was conducted to investigate the UUM students' level of awareness, degree of attitude, and extent of knowledge, as well as their relationship with green practices. The main method used in this study is quantitative, where a survey was conducted to collect primary data. A total of 260 UUM undergraduate students from different colleges were participated in the survey. The data is analysed by using SPSS v24. This study could provide a reference to UUM to find a better way to reduce the environmental problem.